Meeting the mental health needs of care providers - Ajduković, Dean (Array, 1996)
Recognizing the need to address the mental health issues for care-providers and the fact that appropriate self-care skills are rarely part of professional training, the Society for Psychological Assistance (SPA), a Croatian-based mental health non-governmental, non-profit organization, developed a training curriculum aimed at building the professional stress self-management skills and increasing the capacity to prevent own burnout and vicarious traumatization. It was offered to 283 professionals and paraprofessionals that work as care-providers with traumatized and distressed victims of war, especially refugees and displaced people. The subjects had diverse professional backgrounds, ranging from formal psychological, social work or medical (professionals) to legal or educational (paraprofessionals). Both the informal feedback received during the seminar, and the written anonymous evaluations showed that the program was well received and very needed. The mean evaluations provided by the participants were all above 4.2. The pre- and post-intervention comparison of the mean scores revealed a highly significant reduction on three measures (reduction in symptoms, bettert time management and increased role clarity) indicating that the training program was in all probability effective.